RELEVANSI NALAR HUMANISME JHON LOCKE TERHADAP PERSOALAN KEANEKARAGAMAN INDONESIA - Abu Muslim (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
This article studies and analyzes John Locke's view on human rights synthesized to multicultural society in Indonesia. This article departs on the problem of truth claim that implied on the discrimination against some people. Concerning this problem is interesting for the author, if it is based on the view of John Locke on the human rights. According to Locke, since their birth, human have right to live, to free, and to own. Concerning Indonesiacondition that is multicultural, the fundamental basis is needed to think, to do the activities in the state that is aiming to eliminate the oppression and willing to realize the peace in Indonesia.